Upregulation of DGCR8, a Candidate Predisposing to Schizophrenia in Han Chinese, Contributes to Phenotypic Deficits and Neuronal Migration Delay - Bi, Yan; Chen, Shiqing; Shen, Qi; Guo, Zhenming; Ren, Decheng; Yuan, Fan; Niu, Weibo; Ji, Lei; Liu, Liangjie; Han, Ke; Yu, Tao; Yang, Fengping; et al. (Frontiers in Psychiatry, 2022)
Digeorge Syndrome Critical Region Gene 8 (DGCR8) is a key component of the microprocessor complex governing the maturation of most microRNAs, some of which participate in schizophrenia and neural development. Previous studies have found that the 22q11.2 locus, containing DGCR8, confers a risk of schizophrenia. However, the role of DGCR8 in schizophrenia and the early stage of neural development has remained unknown. In the present study, we try to identify the role of DGCR8 in schizophrenia from human samples and animal models. We found that the G allele and GG genotype of rs3757 in DGCR8 conferred a higher risk of schizophrenia, which likely resulted from higher expression of DGCR8 according to our test of dual-luciferase reporter system. Employed overexpression model in utero and adult mice, we also revealed that the aberrant increase of Dgcr8 delayed neuronal migration during embryological development and consequently triggered abnormal behaviors seen in human schizophrenia. Together, these results demonstrate that DGCR8 may play a role in the etiology of schizophrenia through regulating neural development.